REFORMULATION OF LEGAL REGULATIONS CONCERNING ALCOHOLIC BEVERAGES IN BALI WITH LEGAL CERTAINTY AND BENEFIT - Yogi Yasa Wedha; Edy Nurcahyo; Hudali Mukti (Jurnal Scientia, 2023)
Legal arrangements regarding control, supervision, determination of areas/places of sale, authority to issue alcoholic beverage permits and provisions regarding the regulation of traditional alcoholic beverages have urgency, considering that Bali is one of the domestic and international tourist destinations. That traditional alcoholic drinks are also used as a complementary means of religious ceremonies. Researchers see that there has been a legal vacuum after Presidential Regulation No. 74 of 2013 was issued concerning Control and Supervision of Alcoholic Beverages. This situation can certainly raise the issue of legal uncertainty. This article is a normative legal research, using a statutory, historical, and conceptual approach. The research results show that Presidential Regulation (Perpres) No. 74 of 2013 and Law no. 23 of 2014 explicitly regulates control, supervision, determination of places to sell alcoholic and traditional alcoholic beverages and regulates the authority to grant business licenses. Regulations regarding alcoholic beverages have been regulated in laws and presidential regulations, these provisions should be followed up immediately by issuing regional regulations as the implementation of the regulations above, based on the principle of hierarchy, thereby providing legal certainty and providing benefits to the wider community.